Analisis Perbuatan Melawan Hukum Pemerintah Atas Kelalaian Yang Tidak Memperbaiki Jalan Rusak Di Semarang - Fatimah Gufron; Aliffia Intan Maharani; Fildzah Hanifati Nadhilah (Jurnal Ilmiah Wahana Pendidikan, 2023)
There are elements that result in an accident on the highway. These elements include damaged roads. Damaged roads based on applicable regulations illustrate that it is the government's responsibility to carry out their authority as road administrators, be it the central government, regional governments, whether provincial or district/city. The obligation of road administrators is based on the fact that there are credible facts about the occurrence of accident cases as a result of neglect by the organizers due to the lack of government attention regarding road damage in a relatively long period of time. This government negligence becomes a condition as a result of government activities which are considered to have harmed the community. A government that does not carry out an obligation that is under the authority to repair damaged roads which results in losses for the community and takes many victims. The City Regional Head Government is responsible not only for the losses caused by his actions, but also for the losses suffered by other people, namely being responsible for material losses caused by his negligence.